Effect of Local Infiltration Analgesia on Functional Outcomes in Total Knee Arthroplasty: A Randomized, Placebo-Controlled, Double-Blind Clinical Trial - Unver, Bayram; Yuksel, Ertugrul; Eymir, Musa; Maltepe, Fikret; Karatosun, Vasfi (The Journal of Knee Surgery, 2020)
Local infiltration analgesia (LIA) is a simple, surgeon-administered technique for the treatment of postoperative pain after total knee arthroplasty (TKA). The aim of the study was to investigate the efficacy of LIA and its effects on functional outcomes in TKA. A total of 135 patients with primary TKA were recruited and randomized either to receive LIA or to receive placebo injection (PI). Pain, active range of motion (ROM), knee function score, functional activities, and hospital length of stay (LOS) were assessed before surgery and from postoperative day (POD) 1 to at discharge. Lower pain scores at rest were recorded on POD1 and POD2 in the LIA group (p = 0.027 and p = 0.020, respectively). Lower pain score on walking was recorded on POD1 in the LIA group (p = 0.002). There was a statistically significant difference in active knee flexion between groups on POD1 (p = 0.038). There was a significant difference in LOS between LIA and PI groups. Shorter stay was seen in LIA group. There were no statistically significant differences between the groups in terms of knee function score and functional outcomes. LIA technique is effective for pain management in the early postoperative period. LIA added benefit for knee function in terms of active knee flexion ROM after TKA. A shorter hospital LOS was observed in LIA group. However, we did not find any differences in groups in terms of functional assessment such as ability to rise from a chair and walking capacity.The level of evidence is randomized controlled trial, level I.
Keywords: local infiltration analgesia; total knee arthroplasty; functional outcomes; pain; range of motion; knee function score; hospital length of stay